Evidence for overuse of medical services around the world - Brownlee, Shannon; Chalkidou, Kalipso; Doust, Jenny; Elshaug, Adam G; Glasziou, Paul; Heath, Iona; Nagpal, Somil; Saini, Vikas; Srivastava, Divya; Chalmers, Kelsey; Korenstein, Deborah (The Lancet (British edition), 2017)
Overuse, which is defined as the provision of medical services that are more likely to cause harm than good, is a pervasive problem. Direct measurement of overuse through documentation of delivery of inappropriate services is challenging given the difficulty of defining appropriate care for patients with individual preferences and needs; overuse can also be measured indirectly through examination of unwarranted geographical variations in prevalence of procedures and care intensity. Despite the challenges, the high prevalence of overuse is well documented in high-income countries across a wide range of services and is increasingly recognised in low-income countries. Overuse of unneeded services can harm patients physically and psychologically, and can harm health systems by wasting resources and deflecting investments in both public health and social spending, which is known to contribute to health. Although harms from overuse have not been well quantified and trends have not been well described, overuse is likely to be increasing worldwide.